121 ARSACS: a novel phenotype causing peripheral neuropathy, ataxia and spasticity with supranuclear gaze palsy, myoclonus and epilepsy. Issue 3 (9th February 2012) - Stevens, J; Murphy, S M; Davagnanam, I; Phadke, R; Bremner, F; Anderson, G; Nethisinghe, S; Giunti, P; Reilly, M M
Abstract : The phenotype of Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS) was initially reported as early-onset limb ataxia, spastic paraparesis and sensorimotor neuropathy with dysarthria, retinal abnormalities, horizontal nystagmus, urinary dysfunction and mitral valve prolapse in patients from North-Eastern Quebec. The identification of recessive mutations in the SACS gene as the cause of ARSACS has allowed genetically-based diagnoses to be made. Subsequent reports from areas outside of Quebec have broadened the ARSACS phenotype to include adult onset as well as patients presenting with only one or two of the triad of spasticity, ataxia and neuropathy. We describe a patient with genetically confirmed ARSACS whose clinical features comprise spasticity, ataxia and neuropathy but also features not previously described in ARSACS including supranuclear gaze palsy, myoclonus and epilepsy as well as unusual skin biopsy findings. Sequencing of the SACS gene revealed that he was compound heterozygous for two novel mutations, further broadening the phenotype and genotype of this increasingly recognised condition.